The Vagus Nerve in the Neuro-Immune Axis: Implications in the Pathology of the Gastrointestinal Tract - Bonaz, Bruno; Sinniger, Valérie; Pellissier, Sonia (Frontiers in Immunology, 2017)
The vagus nerve (VN) is the longest nerve of the organism and a major component of the parasympathetic nervous system which, together with the sympathetic nervous system, constitutes the autonomic nervous system. There is classically a balance between the sympathetic and parasympathetic nervous systems which is responsible for the maintenance of homeostasis. An imbalance of the autonomic nervous system is observed in various pathologic conditions. The VN is a mixed nerve with 80% of afferent and 20% of efferent fibers and a key component of the neuro-immune axis and the brain-gut axis through a bidirectional communication between the brain and the gastrointestinal tract. A dual anti-inflammatory role of the VN is observed through the hypothalamic-pituitary adrenal axis (activation of vagal afferents) and the cholinergic anti-inflammatory pathway (activation of vagal efferents). The sympathetic nervous system and the VN act in synergy, through the splenic nerve, to inhibit the release of tumor necrosis factor alpha (TNF) by macrophages of the peripheral tissues and the spleen. Because of its anti-inflammatory effect, the VN is a therapeutic target in the treatment of chronic inflammatory disorders where TNF is a key component. In this review, we will focus on the anti-inflammatory role of the VN in inflammatory disorders of the gastrointestinal tract. The anti-inflammatory properties of the VN could be targeted pharmacologically, with enteral nutrition, by VN stimulation (VNS), with complementary medicines or by physical exercise. VNS, used in the treatment of drug resistant epilepsy and depression, could be an effective tool as a non-drug therapy to treat inflammatory disorders of the gastrointestinal tract, such as inflammatory bowel diseases, irritable bowel syndrome, and postoperative ileus which are all characterized by an autonomic imbalance with a low vagal tone.